The Intellectual as a Contemporary Phenomenon - Bové, Paul (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1992)
A reading of Spinoza and Negri in order to rethink the terms of intellectual contemporaneity in liberatory rather than merely historical terms.